EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN PENDEKATAN UKHUWWAH ISLAMIYAH UNTUK MENINGKATKAN SELF ESTEEM REMAJA - Rambe, Malim Soleh; Pasaribu, Muksana; Dongoran, Awaluddin (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This research was motivated by DM Triguna Padang High School students' low self-esteem, which made them not respect themselves. Adolescents with low self-esteem will feel dissatisfied with themselves, withdraw from the environment, be sensitive, put themselves down, and be excessively egocentric. This research aims to analyze the effectiveness of group guidance using the khutbah Islamiyah approach to increase teenagers' self-esteem. The research method used was a quasi-experimental model experiment with a static group comparison design. The population in this study was 220 students, and the sample for this study was 10 students. The research instrument was the Adolescent Self-Esteem Scale, which was proposed using a Likert scale measurement. The data was analyzed using descriptive correlation statistics with the help of SPSS version 25.00. The study results showed that teenagers' self-esteem before treatment was in the low category, while after treatment, it was in the high category. There was an increase in teenagers' self-esteem before and after being given group guidance treatment using the khutbah Islamiyah approach. In this way, group guidance using the khutbah Islamiyah approach can provide effective results for efforts to increase or develop self-esteem in teenagers. This is evidenced by teenagers increasingly having general, social, and personal self-confidence.